2020
DOI: 10.1002/anie.202002923
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Nitrogen towards Direct Nitrate Production on Spinel Oxides

Abstract: Supporting information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
99
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 37 publications
0
99
0
1
Order By: Relevance
“…Dai et al 40 recently looked at the nitrogen oxidation reaction (NOR) catalysed by Fe/Co spinel oxides in alkaline electrolyte. Where they show that adsorbed N 2 is oxidised to intermediate NO x species by the adsorbed OH and the OER intermediate O(OOH) according to eqn (3) and (4):…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al 40 recently looked at the nitrogen oxidation reaction (NOR) catalysed by Fe/Co spinel oxides in alkaline electrolyte. Where they show that adsorbed N 2 is oxidised to intermediate NO x species by the adsorbed OH and the OER intermediate O(OOH) according to eqn (3) and (4):…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…This supercial CoO(OH) enriched surface layer has a benecial effect on the OER for the oxides. 40,41 However, in the presence of surface nitrogen based species, the stabilised CoO(OH) contribute to both the NOR and OER. 40 Kato and Kudo 42 looked at numerous tantalate oxide photocatalysts, and the authors observed nitrate reduction under UV irradiation in an aqueous environment.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…[5] Very recently, Xu and Zhang et al further validated the promising potential of this strategy by adopting spinel oxide and Fe-SnO 2 as electrocatalysts. [6] However, the competitive oxygen evolution reaction (OER) and the complicated fiveelectron oxidation course retarded the development of this technology. Moreover, the structure of electrocatalysts may evolve during the electrooxidation process, and thus probing the active species for NOR is critical for the rational design and synthesis of efficient nitrogen-to-nitrate electrocatalysts.…”
mentioning
confidence: 99%
“…Reproduced with permission: Copyright 2020, Wiley-VCH. Co 2−x O 4 spinel oxides were also utilized as catalysts to carry out electrocatalytic NOR,123 which achieved the direct synthesis of nitrate with high yield (130 ± 12 μmol/ hr/g MO at 1.6 V vs RHE) by iron catalysts (Figure8B,C). Besides, modified MXene electrocatalysts have also been utilized as electrocatalyst for NOR, which achieved 2.80 μg/hr/mg cat yield of nitrate (Figure…”
mentioning
confidence: 99%
“…123 D, Scanning electron microscopy, transmission electron microscopy, and high-resolution transmission electron microscopy images of prepared Pd-MXene, respectively. Reproduced with permission: Copyright 2020, The Royal Society of Chemistry124 Currently, the main catalysts are metal oxides and their composites.…”
mentioning
confidence: 99%